Navigating through the Mundellian Trilemma: A dataset of four decades - Stojkov, Aleksandar; Warin, Thierry (Data in brief, 2019)
The Mundellian Trilemma has maintained its reputation of a sensible guiding framework regarding policy trade-offs among monetary independence, degree of exchange rate flexibility, and financial openness. This data article offers a unique access to explore the determinants and implications of different Trilemma configurations across 195 countries and over 58 years by providing macroeconomic, financial and policy choice data for 103 variables. The dataset has the potential to contribute to the investigation of the consequences of different Trilemma configurations by income group, size, and geographical position of the economies; to enrich international macroeconomics literature on the role of country idiosyncrasies in navigating through the Mundellian Trilemma, and to formulate policy-relevant conclusions.